2023
DOI: 10.3389/ffgc.2023.1182834
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for deploying microbes against tree-killing beetles (Coleoptera) in Anthropocene

Sumanti Gupta,
Amrita Chakraborty,
Amit Roy

Abstract: Forests form rich biodiversity hubs that act as large reservoirs of natural carbon. The spatial and temporal heterogeneity of these complex habitats of forest floors provides ecological services of immense socio-economic importance. However, these socio-economic ecological hotspots are incessantly exposed to multifarious abiotic, biotic, and anthropogenic disturbances, amongst which unpredictable forest pest (i.e., bark beetle) outbreak account for the loss of vegetation and microbiome of measurable quantum. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 255 publications
0
6
0
Order By: Relevance
“…Current data will facilitate further downstream studies (metatranscriptomics, metaproteomics, and culture-based bacterial functional characterization) to characterize the critical bacterial species aiding these Ips beetles thriving on defence-rich pine trees. Such essential bacterial partners can be used for microbiome-based sustainable pest management practices (91, 101, 102). Finally, such knowledge can serve as a primer to decipher the underlying microbial interactions at the tree-beetle interface and facilitate the integration of tree-beetle-microbiome interaction data into spatial models of forest ecosystem dynamics predictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current data will facilitate further downstream studies (metatranscriptomics, metaproteomics, and culture-based bacterial functional characterization) to characterize the critical bacterial species aiding these Ips beetles thriving on defence-rich pine trees. Such essential bacterial partners can be used for microbiome-based sustainable pest management practices (91, 101, 102). Finally, such knowledge can serve as a primer to decipher the underlying microbial interactions at the tree-beetle interface and facilitate the integration of tree-beetle-microbiome interaction data into spatial models of forest ecosystem dynamics predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Other core members such as Dyella, Pseudoxanthomonas, Sphingomonas, Saccharomonospora, Acidisoma have the enzymatic competency to help the beetle metabolize complex carbohydrates found in the conifer cell wall (21,69,(87)(88)(89)(90). Therefore, such microbes belonging to the core bacteriome can be further evaluated in beetlo for potential benefits and targeted for future microbesmediated sustainable beetle management practices (91).…”
Section: Discussionmentioning
confidence: 99%
“…Our colleagues from the United States are deploying fungal-induced gene silencing (FIGS) technology to manage bark beetles, i.e., genetically modifying the bark beetle-associated yeast Ogataea pini, to generate specific dsRNA molecules that target Ips calligraphus (information based on personal communication). Our team has also successfully identified and isolated insectsymbiotic bacteria and fungi (Chakraborty et al, 2020a(Chakraborty et al, ,b, 2023b and may use them as a CSMR for tropical application to control the bark beetles and termites (Gupta et al, 2023). Recently, our group identified 69 core bacterial genera and 19 fungal genera among six bark beetles (Ips typographus, Ips duplicatus, Ips cembrae; Ips sexdentatus, Ips acuminatus, and Polygraphus poligraphus).…”
Section: Chitosan Encapsulated Microbes: New Hope Against Forest Inse...mentioning
confidence: 95%
“…Moreover, within termite-infested wood, fungal communities affiliated with the Eurotiales, Sordariales, Hypocreales, Trichospornales, and Ophiostomatales orders were identified, notably, the fungal genera Apiotrichum, Fusarium, Hawksworthiomyces, Lasiodiplodia, Sporothrix, Trichosporon, and Trichoderma displayed substantial prevalence in the termite-infested wood. As described thoroughly in our recent review, some identified microbial associates of bark beetle or termites can be good candidates for Symbiont-mediated RNAi or SMR (Gupta et al, 2023). Nevertheless, SMR technology can be considered for its potential in forest conservation; additional refinements are necessary before applications.…”
Section: Chitosan Encapsulated Microbes: New Hope Against Forest Inse...mentioning
confidence: 99%
“…Recently, Mogilicherla and Roy (2023b) comprehensively reviewed chitosan-dsRNA nanopesticides and their applications in managing bark beetles. The bacteria and fungi that live symbiotically with bark beetles have been successfully isolated and identified and can be considered putative candidates for symbiont-mediated RNAi (SMT) for tropical application to control bark beetles (Chakraborty et al 2020a(Chakraborty et al , 2020b(Chakraborty et al , 2023Gupta et al 2023;Mogilicherla and Roy 2023b). These studies may pave the way for developing and using RNAi-biopesticides as a secure, efficient, and innovative method to safeguard forest trees.…”
Section: Rna Interference (Rnai)mentioning
confidence: 99%